Disparities in Contraceptive Access and Provision - Casey, Frances; Gomez-Lobo, Veronica (Seminars in Reproductive Medicine, 2013)
Even though contraceptive coverage expands under the Patient Protection and Affordable Care Act, reducing disparities in contraceptive access and provision requires that all providers assess their patient's reproductive life plans and that health systems work to minimize institutional and socioeconomic barriers. In this article, the challenges of providing equal access to contraceptive care, as well as recommendations for encouraging the use of effective contraception among all reproductive age women are reviewed.
Keywords: contraception; access to health services